The Conditions of women’s work in Saudi system and Islamic law - Ibrahim, Mohamed (Journal of Legal Sciences, 2023)
The research dealt with the permissibility and impermissibility of women working according to Islamic law. And the conditions of women’s work in Islamic jurisprudence and Saudi systems such as the work system, civil service, and other systems. The research problem is represented in: Did the Islamic Sharia and the Saudi regulations (laws) allow women to work in private and public jobs? And how to solve the problem of some customs, traditions and norms in Saudi society that stand against women’s work despite women’s need to work? Are all jobs suitable for women? What is the philosophy of the Saudi legislator regarding the participation of women in some jobs and preventing them in others for religious and social reasons? The research reached the most important results, including that Islamic jurisprudence differed in interpreting the sources of women taking over work because they differed in understanding the source that permitted and prevented women from taking over some work. The research also concluded that what is in force in Saudi Arabia agrees with the opinion of some jurists who prevented women from holding certain positions, such as the presidency of the state and the Shura Council or taking over any ministry. The highest position held by Saudi women so far is assistant speaker of the Shura Council, assistant minister, ambassador with the rank of minister, and director of a public university.